The role of verbal painting in Leonid Leonov’s novel “Russian Forest” - Lina Shi; Irina G. Mineralova (RUDN Journal of Studies in Literature and Journalism, 2023)
L.M. Leonov dreamed of becoming an artist and the painter’s talent was embodied in his prose. His landscapes, portraits, portraits against the background of a forest in the tradition of, for example, M.V. Nesterov play an important role in the internal form of his works. The novel “Russian Forest” is indicative in this regard. The purpose of the study is to explain the functions of pictorial allusions and ekphrasis in this novel. The following tasks are solved: identify the most common allusions and ekphrasis in the paintings of Russian artists, which were popular at the time of Leonov painting training, and were subsequently paraphrased in the novel; explain the functions of recognizable paintings by masters of fine art in word painting; argue for the special role of pictorial ekphrasis in the formation of the genre diversity of the novel. As a result, some essential features of the writer’s individual style in the novel under study are clarified: the prose writer’s special attention to the descriptive component of the work makes it possible to assert that his appeal to analogies with fine art is deliberate, since they contribute to the creation of not just a scientific-production or abstract-philosophical novel, but builds a whole series of genre lines, which are supported by recognizable pictorial visualization, on the one hand, and, on the other, forms a deep socio-psychological and lyrical plan of the work. Comparisons of specific paintings transformed into ekphrasis in prose provide scientists with rich material for drawing conclusions about the synthesis of painting and prose.